OPTICAL LUMINOSITY OF ACTIVE GALACTIC NUCLEI AND THE INTENSITY OF ITS HARD RADIATION I - Doikov, D. N.; Yushchenko, A. V. (Одеські астрономічні публікації, 2019)
In this paper, we determine the causes of correlations between the observed logarithmic lu- minosity logL of galaxies with active nuclei (AGN) with particular attention to BL Lac type objects. The properties of flux variations of these galaxies in γ-rays (logL γ ) and in optics (logL O ) are associated with the combined action of cosmic rays (CR), and also with hard radiation around the entire perimeter of AGN. The necessity of using positron spectroscopy in such objects is found. The importance of high-precision measurements of 1.022 MeV line arising from the anni- hilation of positrons with K-electrons of multielectron atoms in the interstellar medium of disk component of the studied galaxies is emphasized. The relation- ship between the single-photon positron annihilation and the Doppler line broadening of the same atoms in optics is investigated in AGN. We found that indi- rect evidence of the presence of a sufficient number of positrons and their annihilation are the cascade chan- nels observed in the form of ∆-resonance. According to the available data from the AGN’s catalogs the cal- ibration of their luminosity in other spectral regions is proposed.